The effectiveness and cost-effectiveness of acupressure for the control and management of chemotherapy-related acute and delayed nausea: Assessment of Nausea in Chemotherapy Research (ANCHoR), a randomised controlled trial - A Molassiotis; W Russell; J Hughes; M Breckons; M Lloyd-Williams; J Richardson; C Hulme; S Brearley; M Campbell; A Garrow; WD Ryder (Health Technology Assessment, 2013)
Background: Chemotherapy-induced nausea and vomiting remain difficult symptoms to manage in clinical practice. As standard antiemetic drugs do not fully eliminate these symptoms, it is important to explore the adjuvant role of non-pharmacological and complementary therapies in antiemetic management approaches. Acupressure is one such treatment showing highly suggestive evidence so far of a positive effect, meriting further investigation. Objectives: The primary objective was to assess the effectiveness and cost-effectiveness of self-acupressure using wristbands compared with sham acupressure wristbands and standard care alone in the management of chemotherapy-induced nausea. Secondary objectives included assessment of the effectiveness and cost-effectiveness of the wristbands in relation to vomiting and quality of life and exploration of any age, gender and emetogenic risk effects. Design: Randomised three-arm sham-controlled trial (Assessment of Nausea in Chemotherapy Research or ANCHoR) with an economic evaluation. Arms include the wristband arm, the sham wristband arm and the standard care only arm. Randomisation consisted of minimisation with a random element balancing for gender, age (16–24, > 24–50, > 50 years) and three levels of emetogenic chemotherapy (low, moderate and high). Qualitative interviews were incorporated to shed more light on the quantitative findings. Setting: Outpatient chemotherapy clinics in three regions in the UK involving 14 different cancer units/centres. Participants: Chemotherapy-naive cancer patients receiving chemotherapy of low, moderate and high emetogenic risk. Intervention: The intervention was acupressure wristbands pressing the P6 point (anterior surface of the forearm). Main outcome measures: The Rhodes Index for Nausea/Vomiting, the Multinational Association of Supportive Care in Cancer (MASCC) Antiemesis Tool and the Functional Assessment of Cancer Therapy – General (FACT-G). At baseline participants completed measures of anxiety/depression, nausea/vomiting expectation and expectations from using the wristbands. Results: In total, 500 patients were randomised in the study arms (166 standard care, 166 sham acupressure and 168 acupressure) and data were available for 361 participants for the primary outcome. The primary outcome analysis (nausea in cycle 1) revealed no statistically significant differences between the three arms, although the median nausea experience in patients using wristbands (both real and sham ones) was somewhat lower than that in the antiemetics only group (median nausea experience scores for the four cycles: standard care arm 1.43, 1.71, 1.14, 1.14; sham acupressure arm 0.57, 0.71, 0.71, 0.43; acupressure arm 1.00, 0.93, 0.43, 0). A gender effect was evident (p = 0.002), with women responding more favourably to the use of sham acupressure wristbands than men (odds ratio 0.35 for men and 2.02 for women in the sham acupressure group; 1.27 for men and 1.17 for women in the acupressure group). This suggests a placebo effect. No significant differences were detected in relation to vomiting outcomes, anxiety and quality of life. Some transient adverse effects were reported, including tightness in the area of the wristbands, feeling uncomfortable when wearing them and minor swelling in the wristband area (n = 6).There were no statistically significant cost differences associated with the use of real acupressure bands (£70.66 for the acupressure group, £111.13 for the standard care group and £161.92 for the sham acupressure group). In total, 26 subjects took part in qualitative interviews. The qualitative data suggested that participants perceived the wristbands (both real and sham) as effective and helpful in managing their nausea during chemotherapy. Conclusions: There were no statistically significant differences between the three arms in terms of nausea, vomiting and quality of life, although apparent resource use was less in both the real acupressure arm and the sham acupressure arm compared with standard care only; therefore; no clear conclusions can be drawn about the use of acupressure wristbands in the management of chemotherapy-related nausea and vomiting. However, the study provided encouraging evidence in relation to an improved nausea experience and some indications of possible cost savings to warrant further consideration of acupressure both in practice and in further clinical trials. Trial registration: ISRCTN87604299. Source of funding: This project was funded by the NIHR Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 17, No. 26. See the HTA programme website for further project information.